Impact of polyunsaturated vegetable oils on adiponectin levels, glycaemia and blood lipids in individuals with type 2 diabetes: a randomised, double‐blind intervention study. Issue 5 (21st October 2013) - Müllner, E.; Plasser, E.; Brath, H.; Waldschütz, W.; Forster, E.; Kundi, M.; Wagner, K.‐H.
Abstract Background Low adiponectin levels are discussed as risk factor for cardiovascular events. This is of special importance in individuals with type 2 diabetes (T2DM) because they are at higher risk for cardiovascular diseases. The present study aimed to investigate the effect of two plant oils rich in polyunsaturated fatty acids (PUFA), with different content of omega‐3 fatty acids, on adiponectin levels, glucose and lipid metabolism in T2DM individuals treated either with insulin or oral anti‐diabetics (OAD). Methods Ninety‐two subjects with T2DM [34 treated with insulin (T2DM‐Ins) and 58 treated with OAD (T2DM‐OAD)] participated in this randomised, double‐blind, parallel intervention study. Individuals received either 9 g of nut oil (n‐3:n‐6 ratio: 1.3 : 6.1) or mixed oil (n‐3:n‐6 ratio: 0.6 : 5.7) per day for 10 weeks. The fatty acid profile, tocopherol, adiponectin levels and parameters regarding glucose and lipid metabolism were assessed at baseline, during and after the intervention. Results Compliance was confirmed by significant increases in γ‐tocopherol and PUFA in both oil groups. An increase in adiponectin levels in T2DM‐Ins participants (+6.84% in nut oil and +4.47% in mixed oil group after 10 weeks compared to baseline) was observed, albeit not significantly different from T2DM‐OAD individuals (P = 0.051). Lipid and glucose metabolism were not affected by the intervention. Conclusions The present study provides evidence that a small and easy change in dietary behaviour towards better fat quality moderately increases adiponectin levels in T2DM‐Ins subjects, independently of the administered plant oil.